Understanding Cognitive Dissonance of Indian Customers for Financial Products: A Multi-Dimensional Scale Development Approach - Bolia, Brajesh; Jha, Sumi; Jha, Manoj K (Indian Journal of Finance and Banking, 2020)
The aim of the study was to understand the dynamics of cognitive dissonance in the context of financial product purchase. A mixed methodology research approach was undertaken to explore the attitudinal and behavioural dimensions (qualitative) and subsequent empirical validation (quantitative) with a sample of customers of financial products. Qualitative research was conducted through focus group discussions to arrive at a pool of 99 items which were then pruned and validated with the help of academic and industry experts. The items were empirically tested and validated with the help of appropriate statistical tools to arrive at a “5 factor and 25 items” measurement scale for cognitive dissonance. The study found two factors “Emotional Gain” & “Financial Concern” as distinguishing factors emerging out as key findings. The arousal of cognitive dissonance after the purchase decision taken by consumer can be a major concern for marketers as it might result in order cancellations, loss of trust for the brand as well as loss of loyal customers. Measuring dissonance in financial product context post purchase can help marketers devise appropriate strategies to reduce dissonance, thereby retaining and attracting customers.